Analisis Pengaturan Hak Untuk Dilupakan Bagi Anak Korban Tindak Pidana Kekerasan Seksual di Indonesia (RechtJiva, 2024)
The growing incidence of sexual violence in Indonesia has taken children as the victims with the highest number of cases among other cases with victims of other age groups. This problem is alarming, considering that it may threaten the future generations of the nation, contrary to the fact that children must receive special protection. Law Number 12 of 2022 concerning Sexual Violence as a Crime implies that children as the victims of sexual violence are entitled to the right to be taken care of and the right to recovery, in which electronic information and/or documents regarding the violence that the children concerned have suffered from must be deleted. In other words, children should be entitled to the right to be forgotten. This research employed a normative-juridical method and statutory, conceptual, and comparative approaches. The legal materials involved primary and secondary data, obtained from library research. The research results reveal that the Law concerning Sexual Violence Crime has loopholes regarding the right to be forgotten of children as the victims of sexual violence, especially in the scope of the subject matter and the mechanism of the actualization of the right to be forgotten for the children concerned. In other words, this matter needs to be further regulated. Therefore, the Law concerning Sexual Violence Crime needs improvement for a comprehensive regulation of the mechanism of the right to be forgotten for children.